Heavy Ethanol Intoxication Increases Proinflammatory Cytokines and Aggravates Hemorrhagic Shock-Induced Organ Damage in Rats - Tsung-Ming Hu; Ru-Ping Lee; Chung-Jen Lee; Yi-Maun Subeq; Nien-Tsung Lin; Bang-Gee Hsu (Hindawi Limited, 2013)
Hemorrhagic shock (HS) following acute alcohol intoxication can increase proinflammatory cytokine production and induce marked immunosuppression. We investigated the effects of ethanol on physiopathology and cytokine levels following HS in acutely alcohol-intoxicated rats. Rats received an intravenous injection of 5 g/kg ethanol over 3 h followed by HS induced by withdrawal of 40% of total blood volume from a femoral arterial catheter over 30 min. Mean arterial pressure (MAP) and heart rate (HR) were monitored continuously for 48 h after the start of blood withdrawal. Biochemical parameters, including hemoglobin, ethanol, glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), blood urea nitrogen (BUN), creatinine (Cre), lactic dehydrogenase (LDH), and creatine phosphokinase (CPK), were measured at 30 min before induction of HS and 0, 1, 3, 6, 9, 12, 18, 24, and 48 h after HS. Serum tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) levels were measured at 1 and 12 h after HS. The liver, kidneys, and lungs were removed for pathology at 48 h later. HS significantly increased HR, blood GOT, GPT, BUN, Cre, LDH, CPK, TNF-α, and IL-6 levels and decreased hemoglobin and MAP in rats. Acute ethanol intoxication further increased serum levels of GOT, GPT, BUN, Cre, LDH, CPK, TNF-α and IL-6 elevation following HS. Acutely intoxicated rats exacerbated the histopathologic changes in the liver, kidneys, and lungs following HS.